Teacher Talk Patterns in Online Learning of Arabic Speaking Skills - Zahriyatun Naeli Syarof (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2021)
Classroom interaction is an important aspect in language learning, especially in speaking class. interaction occurs between lecturers and students or between students. However, at the end of 2019 there was a covid-19 outbreak around the world, so offline learning turned to online learning. Therefore, the purpose of this study is to find out the pattern of teacher talk that occurs in Arabic speaking class by online. This qualitative study took data from 4 online speaking Arabic skills class meetings through zoom meetings at the Arabic language department at State University of Malang. Data analysis used the FLINT (Foreign Language Interaction Analysis) framework. The results showed that the pattern of teacher talk in the class was very diverse according to the FLINT categories and only a few used native language, and the most dominant is giving information.